2012
DOI: 10.1002/rra.2553
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies Fish Passage Behaviour in a Vertical Slot Fishway on the Richelieu River, Quebec, Canada

Abstract: A shift from target species to ecosystem restoration has generated interest in developing fishways that are capable of passing entire fish communities. Although a number of multispecies fishways now exist in North America, evaluations of these fishways are lacking. We used a passive integrated transponder antenna array to quantify passage success and passage duration of fish using a vertical slot fishway (85 m in length, 2.65 m elevation rise, 12 regular pools and 2 turning basins) at a low head dam on the Ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 46 publications
1
47
1
1
Order By: Relevance
“…As a result of the body shape and timing of their respective spawning migrations, we assumed that the gill net had no effect on the silver and shorthead redhorse passage results. Results from Thiem et al (2013) show river redhorse ascending the fishway mostly during the hours of 11 a.m. to 7 p.m., and therefore, the presence of the gill net may have deterred many fish attempting to reascend the fishway. For comparison, passage success in 2010 at the same fishway was 48.7% for longnose sucker and 75.8% for white sucker (Thiem et al 2013), further demonstrating the rather divergent values in fishway success observed among confamilial species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result of the body shape and timing of their respective spawning migrations, we assumed that the gill net had no effect on the silver and shorthead redhorse passage results. Results from Thiem et al (2013) show river redhorse ascending the fishway mostly during the hours of 11 a.m. to 7 p.m., and therefore, the presence of the gill net may have deterred many fish attempting to reascend the fishway. For comparison, passage success in 2010 at the same fishway was 48.7% for longnose sucker and 75.8% for white sucker (Thiem et al 2013), further demonstrating the rather divergent values in fishway success observed among confamilial species.…”
Section: Discussionmentioning
confidence: 99%
“…The three redhorse species were tagged (silver, ; river, ; shorthead, ) with n p 120 n p 70 n p 120 uniquely coded passive integrated transponder (PIT) tags (23 # 3.85-mm Half Duplex; Texas Instruments, Dallas, TX) inserted into their peritoneal cavity (for more details on the tagging procedure, see Thiem et al 2013). TL of each fish was measured, along with a determination of sex accomplished through visual identification (abdominal pressure and gamete extrusion as well as the presence of tubercles on the caudal fin and snout).…”
Section: Passage Success and Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, because slots extend the full height of the WCS and permit flow throughout the water column (when open), they may facilitate passage of the entire nekton assemblage rather than only some species. In riverine systems, vertical slots incorporated into dam fishways were found to improve passage (Stuart and Mallen-Cooper 1999;Stuart and Berghuis 2002) and provided access for a large portion of the riverine nekton community (Baumgartner et al 2010(Baumgartner et al , 2012Thiem et al 2013).…”
mentioning
confidence: 99%